Μία περίπτωση ἐφαρμογῆς τοῦ βυζαντινοῦ θεσμοῦ τοῦ ἀσύλου στήν Πελοπόννησο: Ἡ προσφυγή τῶν Σλάβων στό ναό τοῦ Ἁγίου Ανδρέα Πατρῶν - ΑΝΑΓΝΩΣΤΑΚΗΣ, Ηλίας; ΛΑΜΠΡΟΠΟΥΛΟΥ, Άννα (Byzantina Symmeikta, 2008)
Ilias Anagnostakis and Anna Lambropoulou An instance of the implementation of the Byzantine institution of asylum in the Peloponnese: the Slavs seek sanctuary in the Church of St Andrew of Patrai The events which took place in the Peloponnese in the early ninth century (c. 800) are recorded in later sources, mostly of the tenth century. Following the establishment of the theme system of territorial administration and the securing of ecclesiastical order in the region, the emperor Nikephoros I, in implementing his new fiscal and economic policy, took steps to increase the number of inhabitants by systematically encouraging the settlement of new population groups from outside the area. It was within this general context and during this same period that the rebellion of the Slavs in Achaia, as described by Constantine VII Porphyrogenitus, needs to be viewed. Clearly, also, the phenomenon needs to be seen within the context of the specific social climate of the region where radical change was taking place and significant breaks with the past were occurring. During the repression of the rebellion the Slavs sought sanctuary in the church of the Apostle Andrew. As a result of this move, however, the rebels were given special treatment as they were viewed as having repented their actions. This was an occurrence whose more general implications are worthy of further study. Looked at from the broader ecclesiastical and political perspective, there are certain characteristic features to be noted in the attitudes towards asylum and the priority ascribed to ecclesiastical over civil law in Constantinople at the end of the eighth and the beginning of the ninth centuries. At the beginning of the ninth century, during the reign of Nikephoros I and while Tarasios was on the patriarchal throne (784-806), the flight of the defeated Slavs to the Church of St Andrew and the relative leniency that was shown them by the state suggest that here we are dealing with an instance of the workings of the institution of sanctuary in Byzantium. While the sources bring in a host of hagiographie and miraculous elements -the standard baggage of accounts of Christianisation and repentance-he flight of the Slavs to the church of the patron saint of the city constitutes, in our opinion, in instance of mass asylum. Moreover, it is interesting to observe that the respective terminology which was used in Porphyrogenitus' account and was in all likelihood included in the sigillion of Nikephoros I relies, in our view, directly on Byzantine legislative reforms concerning sanctuary. This is the first recorded instance of mass asylum and resort to church sanctuary in the middle Byzantine period in the Peloponnese. An effort was made both on the part of the church and the state to find a compromise solution: the former sought recognition of the institution of sanctuary while the latter was concerned to maintain the authority of its judicial and penal organs. The Slavs, who had sought sanctuary in the church, while normally liable to the punishment reserved for insurrection, were in the end granted special treatment. A compromise was found: despite the Slavs' attempt to rebel against the Byzantine authorities, the institution of asylum was fully implemented with the imposition of a number of restrictions and sanctions against the Slav population. The economic side of this treatment, which was generally a feature of the institution of ecclesiastical asylum both in Byzantium and the medieval West, has been well investigated. Indeed, monasticism and land ownership in the region of Bithynia are thought to have developed thanks to the institution of monastic asylum and the geographical boundaries of asylum, and this appears to be the case in the Peloponnese, too, where we see privileges and sigillia being granted for new monasteries and metropoleis in the ninth century. It is particularly interesting to note that the limits of 'rural asylum', i.e. the legal delimitation of the concepts of asylum and imperial donations, are lumped together with the estates of the church or monastery. The transfer of the exploitation of cultivable land to the workers of the monastery or church very often led to the development of settlements in the area. Seen in this light, the introduction of the institution of asylum and its legal delimitation in the case of the ecclesiastical estates of Achaia are directly related to the settlements of the early ninth century. It is probable that in contrast to the case of Syria and Bithynia asylum was not the catalyst behind the gradual settlement of the region of Achaia. However, and more importantly, it did offer solutions to the problems arising from the settlements. In the case of Patrai groups of unruly and discontented peasant populations developed an allegiance to the metropolis and were subsequently integrated to the point that they became entitled to protection from every epinoia adikos ('unjust design'). Subsequent to the Patrai episode - as far as the evidence allows us to construe- the Empire turned its military operations to the unsubdued, mountainous and more southerly regions of the Peloponnese. By contrast, the Slavs of Achaia were granted sigillia guaranteeing protection from any unapproved measures or epinoia adikos of the metropolitan. The flight of the Slavs to the Church of St Andrew following the miraculous intervention of the Apostle Andrew and the repression of the revolt, as well as the special treatment that they then received at the hands of the Byzantine authorities on account of their seeking sanctuary in the church, can be seen to constitute a form of asylum that is entirely consistent with the political and social climate and with the concept of asylum of the age of Nikephoros I. Further investigation of the sigillia and their authenticity and reliability as sources may help to improve our understanding of the implementation and development of the institution of asylum in Byzantium during the reign of Nikephoros I.